Nickel-catalyzed cross-coupling of 2-fluorobenzofurans with arylboronic acids via aromatic C–F bond activation - Fujita, Takeshi; Yabuki, Haruna; Morioka, Ryutaro; Fuchibe, Kohei; Ichikawa, Junji (Beilstein Journal of Organic Chemistry, 2025)
2-Fluorobenzofurans underwent efficient nickel-catalyzed coupling with arylboronic acids through the activation of aromatic C–F bonds. This method allowed us to successfully synthesize a range of 2-arylbenzofurans with various substituents. The reaction, which proceeded under mild conditions, involved β-fluorine elimination from nickelacyclopropanes formed by the interaction of 2-fluorobenzofurans with zero-valent nickel species. This protocol facilitates orthogonal coupling reactions of aromatic C–F and C–Br bonds with arylboronic acids.
Keywords: arylboronic acid; benzofuran; C–F bond activation; cross-coupling; nickel